Literature as a liberating space for 19th century women: a close reading of the selected works of Christina Rossetti, Emily Bronte and Kate Chopin - Esha, Nusrat Yasmin (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2019.